IMPLEMENTASI PENDIDIKAN KARAKTER DI SDI PUUDHOMBO KECAMATAN ENDE KABUPATEN ENDE - Ferdinandus Etuasitus Dole (Universitas Negeri Medan, 2021)
Abstract: Implementation Of Character Education At Sdi Puudhombo, Kecamatan Ende, Ende District. The problems studied in this study 1). How far has the character education been implemented at SDI Puudhombo? 2) What is the cultivation of Character values in students like? and; 3) What are the supporting factors that influence the implementation of character education? This study uses an evaluation research method with a discrepancy model developed by Malcom Provus. Samples were taken from grade IV, V and VI students of SDI Puudhombo. The instrument used in the form of a questionnaire to measure the application of character education with the Guttman scale, while for planting values using a Likert scale. Meanwhile, for the data about the factors that influence the implementation of character education using a questionnaire without scoring. The data were analyzed by means of trend analysis which was converted into mean values with 5 scale of trend criteria. The results of research on the implementation of character education at SDI Puudhombo fall into the category of tending to be Very Good with a percentage of 87.77% or a score of 4.39. The results of research on the inculcation of character values in the character education process at SDI Puudhombo fall into the category of tending to be Very Good with a percentage of 96.5 and a score of 4.82. Tradition factors have a stronger influence on the behavior of students, namely 30.98%, followed by self-factors 28.52%, environmental factors around 26.27% and finally family factors by 14.23%. The negative behavior of students is also influenced by all existing factors, but the factors themselves have a stronger influence, namely 44.19%.Keywords: Character Education, Character Value, Value CultivationAbstrak: Implementation Of Character Education At Sdi Puudhombo, Kecamatan Ende, Ende District. Masalah yang diteliti dalam penelian ini 1). Sejauhmana implementasi pendidikan karakter di SDI Puudhombo ? 2) Seperti apakah penanaman nilai-nilai Karakter dalam diri peserta didik ? dan ; 3) Apa saja faktor-Faktor penunjang yang mempengaruhi implementasi pendidikan karakter? penelitian ini menggunakan metode penelitian evaluasi dengan model kesenjangan atau model diskrepansi (discrepancy model) yang dikembangkan oleh Malcom Provus. sampel diambil dari peserta didik kelas IV, V dan VI SDI Puudhombo. instrumen yang digunakan berupa angket untuk mengukur penerapan pendidikan karakter dengan skala Guttman sedangkan untuk penanaman nilai menggunakan skala Likert. Sementara untuk data tentang faktor yang mempengaruhi implementasi pendidikan karakter menggunakan angket tanpa skoring. Data dianalisis dengan analisa kecenderungan yang dikonversikan dalam nilai rata-rata dengan 5 skala kriteria kecenderungan. Hasil penelitian tentang implementasi Pendidikan Karakter di SDI Puudhombo masuk pada kategori cenderung Sangat Baik Dengan persentasi 87,77% atau skor 4,39. Hasil penelitian tentang Penanaman nilai karakter dalam proses Pendidikan Karakter di SDI Puudhombo masuk pada kategori cenderung Sangat Baik persentasi 96,5 dan skor 4,82. Faktor tradisi lebih kuat mempengaruhi perilaku peserta didik yakni sebesar 30,98%, diikuti faktor diri sendiri 28,52%, faktor lingkungan sekitar 26,27% dan terakhir faktor keluarga sebesar 14,23%. Perilaku peserta didik yang negatif juga dipengaruhi oleh semua faktor yang ada, namun faktor diri sendiri memberi pengaruh yang lebih kuat yakni sebesar 44,19%. Kata Kunci: Pendidikan Karakter, Nilai Karakter, Penanaman Nilai